The Role of Websites 0.3 Information in the Development of EFL University Students Linguistic Competence - Mahmood Jasim, Rafal; Khaled Zakaria, Saif (Opción, 2019)
The present research aims at investigating the role of websites 0.3 information in the development of EFL university student’s linguistic competence. The sample of the research was (42) students in department of tourism and hostelry institutions management. To achieve the aim of the research a list of orally linguistic competence (Listening and Speaking) was used after verifying reliability and validity. The researchers choose the post-test equivalent group of experimental design. Therefore, the first group represents the experimental group (21) students which was taught by using websites 0.3 information, while the second group represents the control group (21) students which was taught by the traditional method. After applying the experiment, the tool (orally test) was applied to both groups. T-test showed the superiority of experimental group over the control group in using websites 0.3 information in developing English language competence. The results indicated that the use of websites 0.3 information helped to increase the linguistic competence for the EFL uni- versity students.